Public Reason and the Limits of Liberal Anti-Racism in Latvia - Dzenovska, D (Routledge, 2011)
My paper is a critical analysis of anti-racist and tolerance promotion initiatives in Latvia. First, I trace the historical and geopolitical conditions that enable the emergence of two discursive positions that are central to arguments about racism - that of liberally inclined tolerance activists and that of Latvians with politically objectionable nationalist sensibilities. Subsequently, I argue that, plagued by developmentalist thinking, anti-racist and tolerance promotion initiatives fail in their analysis of contemporary racism. They posit backward attitudes as the main hindrance to the eradication of racism and displace racism as a constitutive feature of modern political forms onto individual and collective sensibilities. Instead of the fast track diagnosis of racism that animates liberal anti-racism, I suggest that an analysis of racism should integrate attention to the common elements of modern racism across political regimes and the historical particularities that shape public and political subjectivities in concrete places. © 2010 Routledge Journals, Taylor and Francis.